Histological comparison of layer media thickness of pulmonary arteroides between Cobb-Vantress and Ross broiler chicken exposed to hypoxia - Vásquez C., María (2012)
The objective of the present study was to determine the development of the smooth muscle of pulmonary arterioles through the relationship of the smooth muscle layer of pulmonary arteriole/arteriolar diameter (CM/DA). Ninety Cobb-Vantress chicks and 90 Ross chicks were used. Of these, 10 birds were weighed and slaughtered at 1 day of age, and the others were randomly distributed in a group raised at sea level (n=40) and a group raised at 3320 m above the sea level (n=40). Ten birds per group were weighed and slaughtered at 10, 20, 30 and 40 days of age. The CM/DA relation was calculated in lung slides stained with Mallory’s phosphotungstic acid hematoxylin. Birds raised at sea level weighed more than those raised at high altitude (p<0.05), and chicks of the Ross line obtained higher body weight at sea level but lower at high altitude than those of the Cobb-Vantress line (p<0.05). The CM/DA relationship increased in all groups according to age (p<0.05), but the Cobb-Vantress line at sea level showed the higher CM/DA relationship from 20 days of age onwards (p<0.05).